What Would Influence Firm Valuation? Financial Reporting and Shareholder Governance - Hessayri, Manel; Saihi, Malek (International Journal of Economics and Financial Issues, 2017)
Our study aims at providing new insight on firm value effects stressing on ownership structure monitoring role, in addition to the disciplinary role of IFRS reporting to provide high-quality information thereby enhancing equity value. We rely on a sample of financial listed firms in three emerging markets, namely, Morocco, South Africa and Turkey. A panel regression for random effects specification is used to control for IFRS effect and non-monotonic effects of ownership structure on firm value. Our findings support the forcefulness of IFRS standards in reducing information asymmetries between “more” informed and “less” informed investors. In addition, unlike institutions and blockholders, institutional blockholders exhibit a non-monotonic influence on firm value. This finding is consistent with the claim that corporate shareholders’ identities and ownership sizes are likely to differentially influence firm valuation. Keywords: firm value, IFRS reporting, ownership structure. JEL Classification: G3